"Kids like me, we go lightly on the head": Experiences of children with a visual impairment on the physical self-concept. (January 2017) - de Schipper, Tessa; Lieberman, Lauren J; Moody, Brigitte
There has been limited research published investigating the experiences of the children with a visual impairment in physical activity and sports. The aim of the study was to explore the experiences of children with a visual impairment on their physical self-concept (PSC). A hermeneutic phenomenological approach was employed to investigate the experiences of children with a visual impairment. Qualitative interviews were conducted with six children between 10 and 12 years, followed by a thematic content analysis. Within the framework of the PSC, four themes emerged: (1) adaptations, (2) friends, (3) bullying, and (4) eyes and glasses. Findings suggest that children with a visual impairment despite the occurrence of bullying or lack of adaptations in sports of physical activity are satisfied with their physical self and global self-esteem.